2023
DOI: 10.1093/ehjcvp/pvad035
|View full text |Cite
|
Sign up to set email alerts
|

Sodium–glucose cotransporter 2 inhibitor use in early-phase acute coronary syndrome with severe heart failure

Abstract: Aims Sodium—glucose cotransporter 2 inhibitor (SGLT2i) improves clinical outcomes in patients with heart failure (HF), but has limited evidence of SGLT2i use on early-phase acute coronary syndrome (ACS). We determined association of early SGLT2i use compared with either non-SGLT2i or dipeptidyl peptidase 4 inhibitor (DPP4i) in hospitalized patients with ACS. Methods and Results This retrospective cohort study that used the Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Sources: [12][13][14][15][16][18][19][20] SGLT2i, sodium-glucose cotransporter-2 inhibitor; MACE, major adverse cardiovascular events; IV, interval variable; CI, confidence interval; SE, standard error; df, degrees of freedom All-cause mortality and cardiovascular mortality: We included six studies in the pooled analysis of comparing the risk of all-cause mortality between patients in SGLTi and the control group, and the results are shown in Figure 3. Pooled analysis showed that the risk of all-cause mortality was lower in patients receiving SGLTi compared to the control group (RR: 0.71; 95% CI: 0.50, 1.00; p-value: 0.05).…”
Section: Figure 2: Effect Of Sglt2i On Macementioning
confidence: 99%
See 1 more Smart Citation
“…Sources: [12][13][14][15][16][18][19][20] SGLT2i, sodium-glucose cotransporter-2 inhibitor; MACE, major adverse cardiovascular events; IV, interval variable; CI, confidence interval; SE, standard error; df, degrees of freedom All-cause mortality and cardiovascular mortality: We included six studies in the pooled analysis of comparing the risk of all-cause mortality between patients in SGLTi and the control group, and the results are shown in Figure 3. Pooled analysis showed that the risk of all-cause mortality was lower in patients receiving SGLTi compared to the control group (RR: 0.71; 95% CI: 0.50, 1.00; p-value: 0.05).…”
Section: Figure 2: Effect Of Sglt2i On Macementioning
confidence: 99%
“…FIGURE 3: Effect of SGLT2i on all-cause mortalitySources:[14][15][16][17][18]20] SGLT2i, sodium-glucose cotransporter-2 inhibitors; IV, interval variable; CI, confidence interval; SE, standard error; df, degrees of freedom…”
mentioning
confidence: 99%